Evaluation of QTc in Rett syndrome: Correlation with age, severity, and genotype. Issue 6 (10th April 2017) - Crosson, Jane; Srivastava, Siddharth; Bibat, Genila M.; Gupta, Siddharth; Kantipuly, Aditi; Smith‐Hicks, Constance; Myers, Scott M.; Sanyal, Abanti; Yenokyan, Gayane; Brenner, Joel; Naidu, Sakkubai R.
Abstract : Rett syndrome (RTT) is caused by MECP2 mutations, resulting in various neurological symptoms. Prolonged corrected QT interval (QTc) is also reported and is a speculated cause of sudden death in RTT. The purpose of this study was to correlate QTc in RTT patients with age, clinical severity, and genotype. 100 RTT patients (98 females, 2 males) with MECP2 mutations underwent baseline neurological evaluation (KKI‐RTT Severity Scale) and QTc measurement (standard 12 lead electrocardiogram) as part of our prospective natural history study. Mean QTc of the cohort was 422.6 msec, which did not exceed the normal values for age. 7/100 patients (7%) had QTc prolongation (>450 msec). There was a trend for increasing QTc with age and clinical severity ( P  = 0.09). No patients with R106C, R106W, R133C, R168*, R270*, R294*, R306C, R306H, and R306P mutations demonstrated QTc prolongation. There was a relatively high proportion of QTc prolongation in patients with R255* mutations (2/8, 25%) and large deletions (1/4, 25%). The overall presence of QTc prolongation did not correlate with mutation category ( P  = 0.52). Our findings demonstrate that in RTT, the prevalence of QTc prolongation is lower than previously reported. Hence, all RTT patients warrant baseline ECG; if QTc is prolonged, then cardiac followup is warranted. If initial QTc is normal, then annual ECGs, particularly in younger patients, may not be necessary. However, larger sample sizes are needed to solidify the association between QTc and age and clinical severity. The biological and clinical significance of mild QTc prolongation above the normative data remains undetermined.